2018
DOI: 10.1039/c8ra05009k
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics of the refractory organic matter in the anaerobic and aerobic digestates of sewage sludge

Abstract: The chemical characteristics of the refractory organic matter in anaerobic and aerobic digestates are hardly known although they are significant for further improving the degradation of organic matter during sludge digestion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Figure 3b shows the high-resolution C1s spectra of HA and PHA. The binding energy peaks centered at 283.04, 283.82, 286.00, and 287.50 eV for HA and at 283.01, 283.76, 286.00, and 287.48 eV for PHA are assignable to C-C, C-H, C-O, and C=O, respectively (see Supplementary Table S3 online) [27][28][29][30] . Compared with HA, the relative amount of C-C in PHA decreased by 18.5%, while C-H increased by 29.6%, which indicated that the relative proportion of protonated C was higher than that of HA.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3b shows the high-resolution C1s spectra of HA and PHA. The binding energy peaks centered at 283.04, 283.82, 286.00, and 287.50 eV for HA and at 283.01, 283.76, 286.00, and 287.48 eV for PHA are assignable to C-C, C-H, C-O, and C=O, respectively (see Supplementary Table S3 online) [27][28][29][30] . Compared with HA, the relative amount of C-C in PHA decreased by 18.5%, while C-H increased by 29.6%, which indicated that the relative proportion of protonated C was higher than that of HA.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical composition of both feedstocks agree with a study that analyzed the chemical characteristics of sewage sludge and anaerobic digestate. 41 Physicochemical characteristics of SS and digestate are shown on Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is necessary to control the source of antibiotics, such as hospitals, pharmaceutical factories, etc. Common methods for the treatment of antibiotics include hydrogen peroxide oxidation, ozone oxidation, and electrochemical technology; however, there is no method to ensure the stable degradation of all antibiotics [39]. Therefore, the development of a method for online monitoring of the concentration of antibiotics described in this paper can help an advanced treatment system to adjust ozone aeration or drug dosage in time according to the monitoring results to achieve automatic control.…”
Section: Data Preprocessingmentioning
confidence: 99%